IDENTIFIKASI PERILAKU KELUARGA SADAR GIZI (KADARZI) PADA BAYI DAN BALITA DI DESA CEPIRING KABUPATEN KENDAL - Sri Setiasih; Titi Mursiti; Supardi Supardi; Yulia Ermawati (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2020)
The first two early years of life is a crucial period because the baby will grow a lot and develop quickly. Malnutrition in the first two years of life will be permanent, irreversible eventhough the nutritional needs of the next period has been given. The member of family must practice health All the family member implement nutrititonal behaviour to prevent he occuurencess of malnutrition and they are able to overcome the problem of it. The purpose of this study was to identify the levels of nutrittion in infants and toddlers in Cepiring Village Kendal Regency. This research is a descriptive research. The approach used is the survey approach. Respondents who were the subject of this study were families who have babies and toddlers aged 0-59 months. The research used cluster sampling technique, the sample was 45 respondents. The results obtained that 33, 3% respondents gave breastfeeding exclusively, 93 % consumed healthy food everyday, 61 % respondents used iodize salt for cooking everyday, 91,7 % respondents consumed vitamin A and 94,4% went to scale the baby weight regularly to the Posyandu. It can be concluded that the familily nutritional behaviour in Cepiring Village is average good. The suggestion to the mothers who have newborn is to exclusively breastfeeding until 6 months old